(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This article presents a dialogue definition of responsibility that allows us to understand and manage the ethical bases of trust placed in a company. It departs from understanding, from trust as an essential moral resource for the smooth-running of a company, that is, an intangible asset that needs to be understood and managed. Thus the concept of a company’s moral responsibility needs to be defined in precise terms and a distinction must be drawn as regards compliance or social responsibility. The publicity principle is the first step to demonstrate compliance with those social expectations placed in a company. These ideas serve as the foundation here for the construction of an Integrated System in order to manage trust embracing codes, committees and ethical audits.